HUBUNGAN PERILAKU IBU DENGAN STATUS GIZI KURANG ANAK USIA - Suciati Ningsih; Kristiawati Kristiawati; Ilya Krisnana (Pediomaternal Nursing Journal, 2014)
Introduction: Toddler malnutrition occurs because at this stage needs of a larger nutrition and more easy to get malnutrition. Lack of knowledge about nutrition and health in the elderly, especially the mother is one of the causes of malnutrition in toddler. The purpose of this study was to analyze the relation of mother’s feeding behavior between toddler’s malnutrition statuses at Puskesmas Sumurgung Kabupaten Tuban.Method: This study use descriptive correlation with cross-sectional design. The population were all mothers with toddler who have malnutrition status at Sumurgung. Samples was taken by purposive sampling technique with 20 respondents. Data were collected by using questionnaire then analyzed using level of significance p<0.05 by Spearman's Rho correlation test.Results: Result showed that there is a significant relationship between knowledge (p = 0.017; r = 0.529), attitude (p = 0.002; r = 0638), and action (p = 0.003; r = 0.636) with toddler’s malnutrition status.Conclussion: Mother’s feeding behavior has a relation between toddler’s malnutrition statuses. Mothers are expected to provide balanced nutrition to children to prevent malnutrition status in toddler.